Vitamin E stabilizes iron and mitochondrial metabolism in pulmonary fibrosis - Chang, Jing; Wang, Jiahui; Luo, Beibei; Li, Weihao; Xiong, Ziyue; Du, Chaoqi; Wang, Xue; Wang, Yuejiao; Tian, Jingya; Li, Shuxin; Fang, Yue; Li, Longjie; et al. (Frontiers in Pharmacology, 2023)
Pulmonary fibrosis (PF) is a fatal chronic lung disease that causes structural damage and decreased lung function and has a poor prognosis. Currently, there is no medicine that can truly cure PF. Vitamin E (VE) is a group of natural antioxidants with anticancer and antimutagenic properties. There have been a few reports about the attenuation of PF by VE in experimental animals, but the molecular mechanisms are not fully understood. In this study, we first confirmed that VE significantly delayed the progression of bleomycin-induced PF (BLM-PF) and increased the survival rates of experimental mice with PF. VE suppressed the pathological activation and fibrotic differentiation of lung fibroblasts and epithelial-mesenchymal transition and alleviated the inflammatory response in BLM-induced fibrotic lungs and pulmonary epithelial cells in vitro. Importantly, VE reduced BLM-induced ferritin expression in fibrotic lungs, whereas VE did not exhibit iron chelation properties in fibroblasts or epithelial cells in vitro. Furthermore, VE protected against mitochondrial dysmorphology and normalized mitochondrial protein expression in BLM-PF lungs. Consistently, VE suppressed apoptosis in BLM-PF lungs and pulmonary epithelial cells in vitro. Collectively, VE markedly inhibited BLM-induced PF through a complex mechanism, including improving iron metabolism and mitochondrial structure and function, mitigating inflammation, and decreasing the fibrotic functions of fibroblasts and epithelial cells. Therefore, VE presents a highly potential therapeutic against PF due to its multiple protective effects with few side effects.